Emergency remote learning in Morocco as a response to the Covid-19 pandemic: students' perspectives. (2nd January 2023) - Belamghari, Mohamed
ABSTRACT: Covid-19 questioned the flexibility and readiness of countries' educational systems to deal with unforeseen global crises. In March 2020, schools were closed to contain the spread of the virus amongst populations of the world. Distance learning replaced the traditional teacher-centred mode of education, thereby leaving students, perhaps for the first time in their life, to take up their own learning at a distance. While inspired from the undergraduate course of Public Speaking, this article adopted a qualitative case study approach and a comprehensive sample of 165 university students to explore the experience of Moroccan university students with emergency remote learning (ERL) during the COVID19 lockdown. The findings from this study pointed out that insecurity, the absence of intimacy, technical issues and unfairness were the main hurdles that negatively influence participants' online learning process. Despite such challenges, other participants in this study confirmed that they learned how to adapt and solve problems during their online experience. Based on the results of this study, implications for future research and practice are discussed.